Reichskanzler Theobald von Bethmann Hollweg 1909–1921 : Rekonstruktion seines verlorenen Nachlasses. Herausgegeben und bearbeitet von Winfried Baumgart. 2 Teilbände - Baumgart, Winfried 1938- HerausgeberIn (Deutsche Geschichtsquellen des 19. und 20. Jahrhunderts, 2022)
»Imperial Chancellor Theobald von Bethmann Hollweg 1909-1921« Theobald von Bethmann Hollweg was Imperial Chancellor from 1909 to 1917. His private papers were destroyed when the Red Army advanced towards Berlin in spring 1945. The purpose of the book is to reconstruct the documents that got lost. The editor collected about 2000 pieces, mostly unpublished, in a number of archives, among them the Archives of the German Foreign Ministry and of the Imperial Chancellery in Berlin. The documents show Bethmann Hollweg in a new light. They testify that he is one of the most high-standing political figures of 20th-century German and European history